"It needs to be the right blend": a qualitative exploration of remote e-workers' experience and well-being at work. Issue 2 (6th September 2021) - Charalampous, Maria; Grant, Christine Anne; Tramontano, Carlo
Abstract : Purpose: This present qualitative study explores the impact of the remote e-working experience on employees' well-being. Design/methodology/approach: Forty (23 male) remote e-workers working for a British IT company were interviewed about their work-related well-being. Semi-structured interviews were framed within an existing theoretical of work-related well-being; hence, questions targeted five distinct dimensions of affective, professional, social, cognitive and psychosomatic well-being. However, data collection was not constrained by this model, allowing the exploration of other aspects interviewees considered relevant to their work-related well-being. Interview data were analysed using thematic analysis, where key themes emerged. Findings: Findings support the relevance of a multidimensional approach to understanding remote e-workers' well-being as it provides an in-depth understanding of the inter-connectedness between relevant dimensions. Further insight into the overlooked issues of detachment from work and health-related behaviours when e-working remotely is also provided. Practical implications: This study proposes practical implications related to the organisational, managerial and individual level; providing individuals tailored guidance on how to remote e-work effectively and raising the importance of cultural change to support remote e-workers to be open about their working preferences. Originality/value: An original contribution to the field of remote e-working is provided, by adopting a holistic approach to explore well-being, disentangling the interconnections between different well-being dimensions and discussing pivotal contributing factors that seemed to be understudied within extant remote e-working literature.